2018
DOI: 10.1111/resp.13275
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic pleural biopsy improves yield of Xpert MTB/RIF for diagnosis of pleural tuberculosis

Abstract: Thoracoscopic pleural biopsy results in increased sensitivity on Xpert testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 12 publications
2
37
0
3
Order By: Relevance
“…The sensitivity of pleural biopsy is 69–97%, and tends to be higher in HIV‐positive individuals . The technique used to acquire pleural tissue is often dictated by the local expertise and resource availability, and while medical thoracoscopy has a sensitivity of up to 100% for tuberculous pleuritis, and is known to improve the yield for both culture and Xpert, it is not always available . In resource‐limited settings, an ultrasound‐guided closed pleural biopsy represents a reasonable alternative with a diagnostic yield of up to 90% .…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity of pleural biopsy is 69–97%, and tends to be higher in HIV‐positive individuals . The technique used to acquire pleural tissue is often dictated by the local expertise and resource availability, and while medical thoracoscopy has a sensitivity of up to 100% for tuberculous pleuritis, and is known to improve the yield for both culture and Xpert, it is not always available . In resource‐limited settings, an ultrasound‐guided closed pleural biopsy represents a reasonable alternative with a diagnostic yield of up to 90% .…”
Section: Diagnosismentioning
confidence: 99%
“…22,78 The technique used to acquire pleural tissue is often dictated by the local expertise and resource availability, and while medical thoracoscopy has a sensitivity of up to 100% for tuberculous pleuritis, and is known to improve the yield for both culture and Xpert, it is not always available. 3,82,83 In resource-limited settings, an ultrasound-guided closed pleural biopsy represents a reasonable alternative with a diagnostic yield of up to 90%. 84 In this case, the yield is maximized by the use of an Abrams biopsy needle (compared to Tru-Cut needle) and harvesting more than six biopsy specimens.…”
Section: Pleural Biopsymentioning
confidence: 99%
“…Molecular diagnostic tools are increasingly utilized to diagnose TB and detect drug resistance for both pulmonary and extrapulmonary diseases . In a study by Christopher et al , Xpert MTB/RIF assay on the thoracoscopic biopsy gave a substantially higher yield of 45% than biopsy culture (39%), pleural fluid culture (17%) or pleural fluid Xpert MTB/RIF (14%) among 73 patients with TB confirmed by histopathology on thoracoscopic biopsy. Among 61 cases of endobronchial TB diagnosed on bronchoscopic features, histology and positive sputum or tissue TB cultures in another study by Zhang et al , Xpert MTB/RIF performed on bronchoscopic brushing and biopsy had sensitivities of 57% and 64%, respectively, as compared to 13.1%, 32.8%, 36.1% and 68.9% for sputum smear, bronchial brush smear, sputum culture and tissue culture, respectively.…”
Section: Tuberculosismentioning
confidence: 99%
“…13.3% (95% CI: 4-31%); thus, the authors suggested that Xpert was not the ideal diagnostic tool for pleural tuberculosis [24]. The same team improved their methods and increased the sensitivity of Xpert in diagnosing tuberculous pleuritis to 45.0% (95% CI: 32.1-58.4) [14]. They explained that the low sensitivity in their previous study published in 2013 was probably due to the small amount of pleural tissue taken using a closed pleural biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…The pooled sensitivity of Xpert in the diagnosis of tuberculous pleural effusion (TPE) was between 30% and 51% [10][11][12]. Studies have shown that pleural biopsies taken under medical thoracoscopy are better specimens for diagnosing tuberculous pleuritis compared to pleural fluid [9,13,14]. Our group previously evaluated the performance of Xpert on urine specimens for the rapid diagnosis of urinary tract tuberculosis and indicated that Xpert showed a better performance than smears and cultures in detecting urinary tract tuberculosis and that it could be considered for the diagnosis of urinary tract tuberculosis [15].…”
Section: Introductionmentioning
confidence: 99%